Pumps and compressors - Borremans, Marc, 1951- (John Wiley & Sons Ltd ; ASME Press, 2019)
A practical guide to the majority of pumps and compressors used in engineering applications' Pumps and compressors are ubiquitous in industry, used in manufacturing, processing and chemical plant, HVAC installations, aerospace propulsion systems, medical applications, and everywhere else where there is a need to pump liquids, or circulate or compress gasses. This well-illustrated handbook covers the basic function, performance, and applications for the most widely used pump and compressor types available on the market today. It explains how each device operates and includes the governing mathematics needed to calculate device performance such as flow rates and compression. Additionally, real-world issues such as cavitation, and priming are covered. Pumps & Compressors is divided into two sections, each of which offers a notation of variables and an introduction. The Pumps section covers piston pumps, radial turbopumps, axial turbopumps, rotating pumps, hydraulic pumps, and pumps with driving flow. The Compressors section covers piston compressors, rotating compressors, turbo compressors, ejectors, vacuum pumps, and compressors for cooling purposes. -A virtual encyclopedia of all pumps and compressors that describes the mechanics of all devices and the theory, mathematics, and formulas governing their function -Allows the reader to develop the skills needed to confidently select the appropriate pump or compressor type and specification for their applications Pumps & Compressors is an excellent text for courses on pumps and compressors, as well as a valuable reference for professional engineers and laymen seeking knowledge on the topic.
Includes index.
Publishing location for second publisher obtained from publisher's Web site.
Keywords: Pumping machinery.; Compressors.; elektronické knihy; electronic books